Understanding persecution in Matthew 10:16-23 and its implication in the Nigerian church - Peters, Prince E. (HTS teologiese studies, 2020)
The modern use of the word ‘persecution’ in both speeches and books shows a phenomenon that is almost wholly associated with religion. However, persecution is a threat to the peace of religious institutions as well as various societies all over the world; thus, this makes it a phenomenon beyond the scope of religion. However, this research focuses on religious persecution. It studies an aspect of persecution which is called intra muros persecution. This means ‘internal’ persecution. ‘Internal’ in this context describes the kind that existed in the Jewish religious settings, amongst professing Jews, strictly between Rabbinic Jews and Messianic Jews as predicted in Matthew 10:16–23 and is reflected in today’s Christianity in the form of various intra-denominational attacks in Nigeria. The study delves into the history of events which took place between Rabbinic Jews and Messianic Jews and how it relates to the Christian faith, coming out with the discovery that division which it called sectarianism was the brain behind this brand of persecution. The application of the study to the Nigerian situation necessitates the call for tolerance amongst various denominational sects in Nigeria.